The Impact of Urban Rail Transit on Industrial Agglomeration Based on the Intermediary Effects of Factor Agglomeration. (1st February 2021) - Li, Zhonghui; Xia, Tongshui; Xia, Zhiqing; Wang, Xinjun
Abstract : Urban rail transit is an important form of infrastructure for a city or even a country. This paper uses location entropy to measure the industrial agglomeration level of cities at the prefecture level or above in China from 2006 to 2018 and empirically tests the mechanisms of urban rail transit construction, factor agglomeration, and industrial agglomeration. The empirical results show the following: (1) the construction of urban rail transit infrastructure has a significant positive effect on the agglomeration of the labor force, capital, and technological innovation; (2) urban rail transit construction effectively induces agglomeration in the urban manufacturing industry and consumer service industry; and (3) the impact of urban rail transit construction on agglomeration in the urban manufacturing industry and consumer services industry is primarily due to the intermediary effects of factor agglomeration. The results show that gradually improving the urban rail transit network, strengthening the construction of comprehensive rail transit hubs, and optimizing capital allocation within urban rail transit allow for the full utilization of urban rail transit construction in promoting industrial agglomeration.